Size Distribution and Habitat Characteristics of Coconut Crabs (Birgus latro) in Tomajiko, Hiri Island District, Ternate City, Province North Maluku - Rugaya H. Serosero; Yuyun Abubakar; Riyadi Subur; Mesrawati Sabar; Saman; Ariyanti H. Fadel; Rina; Sri Endah Widiyanti; Salim Abubakar (Jurnal Biologi Tropis, 2023)
Coconut crabs (Birgus latro) is a fishery resource that is only found in eastern Indonesia, and the waters of Ternate City are an area that has this potential.  This research aims to determine the size distribution and habitat characteristics of coconut crabs in Tomajiko, Hiri Island District. The data collection method consists of several stages, namely determining stations, distributing bait, catching coconut crabs, morphometric measurements, and observing environmental parameters. Determination of stations in this study was carried out based on topographic differences in Tomajiko (divided into two stations). Coconut crab catching uses the roaming survey method. The bait used is coconut meat that has been split into several parts and coconut meat that has been mashed. The morphometric dimensions measured were chest length (carapace length) and body weight. The habitat characteristics observed were the type and extent of vegetation, organic matter content and substrate texture, environmental parameter measurements (soil temperature, air humidity and soil pH). The results of the research showed that the coconut crabs caught at both stations had relatively the same length, but the largest weight was found at station 2. Habitat characteristics in Tomajiko, Hiri Island strongly support the survival of coconut crabs.